Movimento circular uniforme: aprendizagem pelo modelo da sala de aula invertida (Flipped Classroom) - Barbosa, Paulo Cesar Puga (2016)
This work produced a planning guide for learning the uniform circular motion from the inverted classroom model (flipped classroom). The study was conducted at the Instituto Federal de Educação, Ciência e Tecnologia (IFAM) - Campus Manaus Zona Leste with a group of first year of the integrated technical education with the average. The experience of the class with the uniform rectilinear movement classes and uniformly varied rectilinear motion by the traditional method of teaching physics was important for the application of this research. Thus, the uniform circular motion of the flipped classroom teaching through the structure that broke with the students knew. To apply this method with students used the proposal developed in the e-book of spanish teacheres: Alicia Diez, Javier Tourón and Raúl Santiago. The educational product of this work is the result of the account of my experience with the flipped classroom. In the first part of the educational product, will be fully explained to the teacher working with educational technology tool EDpuzzle and guide their students in the use of it. In the second part, the most important, the teacher will have a lesson plan together scripts for the activities in the classroom. The development of the educational product was made in the light of Bloom's Taxonomy, which guided the definition of learning objectives and also helped to choose which the most appropriate technological tools to achieve these goals. The final comments of feedback show the acceptance of the flipped classroom unanimously by all students and proves the failure of the traditional education system.